Mnemotables as a Means of Developing Coherent Speech in Primary School Children with Mental Retardation - Petrova A. V. (Interactive science, 2023)
the article describes the results of experimental work on the use of mnemotables for the development of coherent speech in younger schoolchildren with mental retardation. The author concludes that the use of mnemonics techniques for the development of coherent speech in children with intellectual disabilities is very effective and has a positive effect on the intellectual development of this category of children.
Keywords: ребенок; младший школьный возраст; связная речь; развитие; речевая деятельность; умственная отсталость; монологическая речь; мнемотаблица; мнемотехника; primary school age; development; monologue speech; child; speech activity; mental retardation; mnemonics; coherent speech; mnemonic table